Diary of An African Hub Manager lessons in growing our innovation system - Mtambalike, Jumanne (India Thomson Press, 2022)
The book combines my experience working in the African innovation ecosystem for the past ten years and scientifically proven methodologies for building robust innovation systems. Less has been told about grassroots innovation ecosystems in Africa. Sometimes, it is from someone who lacks local context and understanding, hence detachment from the reality on the ground?most of what I know about innovation processes in Africa I had difficulty learning.
Keywords: Innovation